Percutaneous Driveline Fracture After Implantation of the HeartMate II Left Ventricular Assist Device: How Durable is Driveline Repair?. Issue 5 (September 2017) - Stulak, John M.; Schettle, Sarah; Haglund, Nicholas; Dunlay, Shannon; Cowger, Jennifer; Shah, Palak; Aaronson, Keith D.; Pagani, Francis D.; Maltais, Simon
Abstract : Durability of the percutaneous driveline is critical for the optimal long-term support of patients after left ventricular assist device (LVAD) implantation. There are no data specifically examining the durability of major repair for driveline fracture or its effect on patient outcomes. Between May 2004 and August 2014, 560 patients underwent implantation with the HeartMate II LVAD at our respective institutions. Median age at LVAD implantation was 59 years (range 18–82 years) and 465 patients (83%) were male. The indication for LVAD implantation was bridge to transplant (BTT) in 296 patients (53%). Follow-up was available in all early survivors (n = 519) for a total of 940 patient-years of support (median 1.1 years, max. 10.4 years). Percutaneous driveline fracture was identified in 17 patients (3.2%), eight of whom were implanted as destination therapy. Median time from LVAD implantation to driveline fracture was 1.3 years (range, from 4 months to 3.8 years). Two of these patients underwent device exchange as primary treatment, while 15/17 (88%) underwent repair. Three of these 15 patients required a driveline reintervention, including device exchange (n = 1), rerepair (n = 1), and ungrounded cables (n = 1). Median time of support after driveline repair was 10 months (range from 3 months to 5.4 years). There were no late deaths after driveline repair during the follow-up period with 14/15 patients (93%) active on support and one having undergone transplant. The incidence of percutaneous driveline fracture after HeartMate II LVAD implantation is low (3.9%). The majority of driveline repairs for driveline fracture are durable with reintervention required in a minority of patients. There was no adverse effect of driveline fracture requiring repair on late outcome noted in this series with all patients either active on support or transplanted at last follow-up.